Dynamics of the three-dimensional primitive equations of large-scale atmosphere. Issue 14 (22nd September 2022) - Zhao, Chunxiang; You, Bo
Abstract : The main objective of this paper is to study the long-time behavior of weak solutions for the three-dimensional primitive equations of large-scale ocean. Due to the low regularity of the triple nonlinearity term, it is very difficult to obtain the uniqueness of weak solutions such that we can not study the long-time behavior of weak solutions by using the classical theory of infinite-dimensional dynamical systems. Inspired by the idea of ℓ-trajectory in [1], we introduce a new phase space X ℓ (see Section 3.1 for the definition of X ℓ ) on which the translation semigroup L ( t ) t ≥ 0 can be imposed naturally. We first establish the finite-dimensional global attractor in X ℓ by using the classical theory of infinite-dimensional dynamical systems, via a Lipschitz continuous mapping from X ℓ into H (see Section 2 for the definition of H ), we obtain the corresponding finite-dimensional global attractor in H .